Establishment of a predictive model for outcomes in patients with severe acute pancreatitis by nucleated red blood cells combined with Charlson complication index and APACHE II score - Xu, Chengxin; Wang, Jing; Jin, Xiaxia; Yuan, Yuan; Lu, Guoguang (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Nucleated red blood cell (NRBC) is an immature red blood cell, which can appear in the peripheral blood of newborns but not in normal adults. However, in the presence of hemorrhage, severe hypoxia, or severe infection, NRBCs may exist in adult blood and are associated with prognosis. The aims of this study were to establish a predictive model for the outcome of patients with severe acute pancreatitis (SAP) based on NRBCs. Materials and Methods: Data from 92 patients with SAP were retrospectively collected for the study. We used chi-square automatic interaction detection (CHAID) to explore a prediction model of mortality in patients with SAP by NRBCs. Results: During the 90-day follow-up, 11 participants (12.0%) died. The NRBC-positive rate of nonsurvivors was much higher than survivors (90.9% vs. 23.5%). Charlson Comorbidity Index (CCI), Acute Physiology and Chronic Health Evaluation II (APACHE II), Ranson score, and serum C-reactive protein were higher in nonsurvivors (5.0, 29.0, 6.0, and 140.0 g/L) than survivors (3.0, 13.0, 4.0, and 54.7 g/L). A CHAID model including NRBC, CCI, APACHE II score, and Ranson score showed that NRBCs differentiated well between nonsurvivors and survivors. All patients with SAP survived when they had a negative test result for NRBCs and CCI was below 7. All patients died when they had a positive test result for NRBCs and APACHE II score exceeded 30. Among patients whose NRBC test result was positive and APACHE II score was below 30, if the Ranson score was less than 5, the mortality rate was only 5.6%, whereas the mortality rate was 66.7% if the Ranson score exceeded 5. A validated population of 32 patients showed that the accuracy of the prediction model was 100%. Conclusion: NRBC combined with CCI, APACHE II, and Ranson score can predict 90-day mortality of patients with SAP.